Be Violent Again: Violence, Realism and Consumerism in Arthur Miller’s Death of a Salesman and Mark Ravenhill’s Shopping and Fucking - Pina Coelho, Rui Manuel (Cartaphilus, 2016)
In this paper I will consider the 1950s as a seminal period for the configuration of violence in modern drama and as a crucial moment for the fusion between violence and realism. In post-war drama, we will not see violence portrayed as an extreme action or as unbelievable acts. Violence becomes the natural way to express social and individual tensions, through class conflicts, strong language and war motives. Themes such as the display of physical violence, the failure of the human body, exposing dysfunctional families and war effects, becomes more and more common and attached to everyday life. This was fertile ground for John Osborne, Edward Bond or Arthur Miller, or for the British dramaturgy of the nineties, especially with the so-called in-yer-face theatre. Thus, I will focus on the effects this global discussion had on Portuguese culture and theatre. I will discuss two performances that are both representative of the Portuguese alternative culture of the time and that stage texts that deal with realistic violence: Arthur Miller’s Death of a Salesman by Experimental Theatre of Oporto (TEP), in 1954; and Mark Ravenhill’s Shopping and Fucking, directed by Gonçalo Amorim, in 2007. Both performances represent straightforward approaches to the texts and raise several interesting aspects: how is violence portrayed inPortugal, in 1954, when a fascist dictatorship imposed a severe censorship on performances? And how is Ravenhill’s violence replaced by irony in the performance by Gonçalo Amorim?